Biogas from waste and renewable resources : an introduction. - Deublein, Dieter, ....-; Steinhauser, Angelika, ....- (Weinheim : Wiley, 2009)
In the face of rising costs for fossil fuels, there is currently a worldwide drive to utilize unused biomass from industrial and household waste, wastewater, farming, and marine sources to generate electricity, fuel and heat. Biogas plants are the most cost-effective way to realize this and can be built and operated in all sizes and under a wide range of conditions. In fact, biogas plants are predicted to take a leading role in renewable resource utilization, in both the developed and the developing world. Written as a practical introduction to biogas plant design and operation, this book fills a huge gap by presenting a systematic guide to this emerging technology -- information otherwise only available in poorly intelligible reports by US governmental and other official agencies. The authors draw on material taught by Prof. Deublein in a university course as well as experiences from a wide variety of industrial biogas projects, thus combining didactical skill with real-life examples. Alongside biological and technical aspects of biogas generation, this timely work also looks at safety and legal aspects as well as environmental considerations and provides ideas to be explored for potential future progress in the development of biogas production technology.
Keywords: Biogas; Duurzame energie